2012
DOI: 10.1074/jbc.m112.412122
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of ATP-sensitive K+ Channels in Cardiac Myocytes

Abstract: Ventricular KATP channels link intracellular energy metabolism to membrane excitability and contractility. We identified plakoglobin (PG) and plakophilin‐2 (PKP2) as KATP channel associated proteins and investigated whether the association of KATP channel subunits with junctional proteins translates to heterogeneous subcellular distribution within a cardiac myocyte. Co‐immunoprecipitation experiments confirmed physical interaction between KATP channels and PKP2 and PG in rat heart. Immunolocalization experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
(55 reference statements)
1
15
0
1
Order By: Relevance
“…These images from each color channel were than superimposed to generate a 2 color superresolved image; the mapping error in this image was 20 nm. The 2 color mapping error obtained was found to be better than 20 nm, as we and others previously reported (39,40,(43)(44)(45).…”
Section: Dual-color Acquisition and Mapping Errorsupporting
confidence: 72%
See 1 more Smart Citation
“…These images from each color channel were than superimposed to generate a 2 color superresolved image; the mapping error in this image was 20 nm. The 2 color mapping error obtained was found to be better than 20 nm, as we and others previously reported (39,40,(43)(44)(45).…”
Section: Dual-color Acquisition and Mapping Errorsupporting
confidence: 72%
“…For accurate alignment and mapping of the 2 color channels, diffraction-limited fluorescent beads were first imaged with emission spectra spanning both channels (Invitrogen). The location of the beads was matched for both channels, and a mapping matrix was generated using an IDL (Exelis Visual Information Solutions) custom mapping routine (39,40,(43)(44)(45). This mapping matrix superimposes the 2 sides of the image, each corresponding to a different color, into a 2-color image, and the images obtained were processed and analyzed using an ImageJ macro routine, which is based on the QuickPALM plugin (46).…”
Section: Dual-color Acquisition and Mapping Errormentioning
confidence: 99%
“…In addition to Na v 1.5 and K ir 2.1, previous studies have reported preferential localization of K V 1.5,(19) the voltage-gated, shaker-related potassium channel, small conductance calcium-activated potassium (SK) channels(26), and K ir 6.2, the ATP-sensitive potassium channel,(9) at the intercalated disc. Also, we have demonstrated that activation of the rapid (HERG)(14) and slow (KvLQT1)(33) delayed rectifier potassium channels as well as K ir 6.2 can modulate cardiac conduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that K ir 6.2 is also located at the intercalated disc and around the sarcolemma. (9) Therefore, the localization-dependent role of potassium channels as direct determinants of cardiac conduction merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of the desmosomal complex in PKP2 deficient mice results in downregulation of K ATP channels, suggesting a possible role of these channels in cell-to-cell communication. 113 …”
Section: Potassium Channel Macromolecular Complexes and Associatedmentioning
confidence: 99%